Contemporary challenges in the management of university alumni associations - Łazorko, Katarzyna (Journal of Management and Financial Sciences, 2025)
Polish organizations gathering alumni, functioning as independent bodies, have recently faced several problems including the generation gap, lack of young members, and problems with fundraising. Operating within existing models is no longer effective due to significant social and economic changes that have taken place in their environment. They need to rethink and redesign their strategies. The model presented in the paper identifies the main areas of the change and the directions that the organizations need to follow to ensure their further effective functioning. The research contributes to the discussion on alumni management in Poland. The topic is marginally explored in Polish scientific literature and the perspective of other countries enables application due to specific characteristics. The discussion in the paper is adjusted to conditions specific to Poland and is focused on organizations of a certain type.